KESALAHAN BERBAHASA BIDANG MORFOLOGI PADA PLATFORM INSTAGRAM - Putri Prastikha, Nadia; Sri Lestari, Pipin; Ahmad Nuridayah, Ramadhan; Markamah, Markamah (Universitas Hamzanwadi, 2024)
This research aims to identify and analyze language errors in the field of morphology found on the Instagram platform. The method used is descriptive qualitative with a content analysis approach to Instagram user uploads and comments. Data is collected from popular accounts and various posts. The research results show that the most frequently occurring morphological errors include the formation of repeated words, the use of inappropriate affixes, and the formation of compound words incorrectly. The main factor causing this error is the user's lack of understanding of standard Indonesian language rules and the influence of slang and foreign languages. It is hoped that these findings can become the basis for efforts to increase language literacy on social media and provide insight for educators and language researchers regarding the phenomenon of language errors in the digital era.